The Citrus Variety Improvement Program in Spain in the Period 1975-2001 - Navarro, Luis; Pina, José A.; Juárez, José; Ballester-Olmos, José F.; Arregui, Juana M.; Ortega, Carmen; Navarro, Antonio; Durán-Vila, Núria; Guerri, José; Moreno, Pedro; Cambra, Mariano; Medina, Alejandro; et al. (IOCV, 2022)
The Citrus Variety Improvement Program in Spain (CVIPS) started in 1975. It has the following objectives: a) to recover pathogen-free plants of local cultivars by shoot-tip grafting in vitro (STG); b) to import foreign genotypes through a STG based quarantine procedure; c) to maintain healthy genotypes in a Germplasm Bank; and d) to release healthy budwood to citrus nurseries through a certification program. Plants recovered by STG are biologically indexed by inoculation to the following indicator plants: Mexican lime, Pineapple sweet orange, Dweet tangor, Citrus excelsa, Etrog citron, and Parson’s Special mandarin. In addition, they are indexed by sPAGE or imprint-hybridization for viroids, by RT-PCR for Citrus leaf blotch virus, by dsRNA analysis for viruses that produce dsRNA during their replication cycle, and by tissue print-ELISA for Citrus tristeza virus. Only healthy genotypes are included in the Germplasm Bank, which has a field collection used for research and horticultural evaluation, a cryo-stored collection for longterm maintenance, and a screen-house collection that is used to release budwood to nurseries. It contains a total of 428 genotypes, 237 selected in Spain and 191 imported from other countries, representing 43 Citrus species and 32 species from 17 Citrus-related genera. Release of healthy budwood from this program to nurseries started in 1979. At that time, there were only 10 registered nurseries, but in the last few years the number has now increased to 39. For commercial propagation all nurseries are using budwood from the Germplasm Bank. Since the beginning of the program, about 85 million certified nursery trees from this origin have been produced. This represents more than 70% of the Spanish citrus industry. The CVIPS has had a very high impact on the citrus industry. Virus and virus-like diseases do not currently induce any significant damage in the new plantings, and a wide selection of healthy material from the best varieties is available for growers.